Our Experience of Conscious Sedation as an Anaesthetic Technique in patients undergoing Automatic Implantable Cardioverter Defibrillator - Choudhury, BMM; Rahman, M; Sultana, R; Beg, AK (Cardiovascular Journal, 2012)
Ten patients with life threatening ventricular arrhythmias who underwent placement of automatic cardioverter defibrillator ( AICD) under conscious sedation are reported. Our clinical experience, patient,s satisfaction, recovery profile and complications of the technique of conscious sedation is presented and discussed. Key words: Ventricular dysrhythmias; Autamatic implantable cardioverter defibrillator; Conscious sedation DOI: http://dx.doi.org/10.3329/cardio.v4i1.9388 Cardiovasc. J. 2011; 4(1): 42-45